Signalling theory as a framework for analysing human resource management processes and integrating human resource attribution theories: A conceptual analysis and empirical exploration. (10th November 2020) - Guest, David E.; Sanders, Karin; Rodrigues, Ricardo; Oliveira, Teresa
Abstract: Signalling theory is presented as an approach to advance the study of human resource management (HRM) processes highlighting line managers as signallers of HR messages and employees as receivers. Signalling theory is also offered as a framework to integrate the two attributional approaches to HRM focusing on HRM strength and HR attributions. A study of employees in 83 bank branches confirms that strong HR signals, reflected in implementation of a coherent set of high‐commitment HR practices and consensus about their implementation have a positive association with the HR attributions and attitudes of employees as signal receivers. We found no link with branch performance. The study confirms the utility of signalling theory as a framework for advancing our understanding of HR processes.